Membangun Karakter Entrepreneur (Wirausaha) Bagi Generasi Muda Di Lingkungan Perguruan Tinggi - Reni Nasrianti; Siti Aminah Nasution; Susiwati; Ervina Ningtias (Kilau Publishing, 2026)
Developing entrepreneurial character in the younger generation is a crucial effort to improve the quality of human resources capable of creating independent business opportunities. This community service activity aims to enhance the understanding, motivation, and entrepreneurial character of university students. The activity was conducted at Rokania University and involved 400 students from various study programs. The method used was entrepreneurship training and mentoring through the stages of needs identification, material delivery, discussion, business idea development simulations, and activity evaluation. Data was collected through observation, documentation, and participant reflection, then analyzed descriptively and qualitatively. The results of the activity showed an increase in students' understanding of the concept of entrepreneurship, their ability to identify business opportunities, and their motivation to start a business. Furthermore, there was a development in entrepreneurial character, demonstrated by increased creativity, innovation, self-confidence, responsibility, discipline, teamwork skills, and risk-taking. The training and mentoring provided were proven effective in developing students' entrepreneurial character, thus providing them with the necessary tools to create independent businesses and increase their competitiveness in the future.